Variations in the anatomical and branching pattern of the left coronary artery: a cadaveric study - S., Lakshmiprabha; Afroze, Khizer Hussain; P., Ramesh; K. R., Asha; C., Shivaleela; D., Anupama (International Journal of Research in Medical Sciences, 2018)
Background: Coronary arteries are the branch of ascending aorta and it is the main arterial supply of the myocardium of the heart. Left coronary artery (LCA) usually arises from left posterior aortic sinus. The site of manifestation of myocardial infarction depends on the occlusion of an artery or its branches involved in atherosclerosis. To know the site of lesion and occlusion of the particular artery, detailed anatomy of its course, branches and variations to be studied in detail. Methods: Study was conducted on 55 heart specimens in Department of Anatomy at Sri Siddhartha Medical College (SSMC), Sri Siddhartha Academy of Higher Education (SSAHE). The left coronary artery was dissected carefully, and it was traced from its origin. Any variation in the course and branching pattern was recorded and photographed. Results: No variation was found in the origin of LCA. In the present study, the most frequent division pattern of the left coronary artery was observed as the bifurcation in 30 specimens (54.54%) followed by trifurcation in 23 specimens (41.82%). Tetrafurcation and pentafurcation of LCA were observed in one specimen each (1.82%). Conclusions: Our study tries to focus on branching pattern of LCA for the better knowledge of accurate diagnosis and therapeutic intervention in the management of coronary artery diseases.